Association of vitamin D with adiposity measures in a cross-sectional study of Cypriot adolescents: Ourania Kolokotroni - Kolokotroni, Ourania; Yiallouros, Panayiotis K.; Papadopoulou, Anna; Raftopoulos, Vasilios; Nicolaidou, Polyxeni; Middleton, Nicos; Kouta, Christiana (My University, 2014)
Lower vitamin D levels have been widely reported in the obese but evidence on the association of vitamin D with adiposity measures beyond the obese status and across the BMI range is limited. This study aimed to assess vitamin D status amongst Cypriot adolescents and investigate the association of vitamin D with two adiposity measures, body mass index (BMI) and body fat percent (BF%).
Keywords: Vitamin D; Adolescents; Predictors; Adiposity; BMI; Body fat percentage